Melanopsin Retinal Ganglion Cells and Pupil: Clinical Implications for Neuro-Ophthalmology - La Morgia, Chiara; Carelli, Valerio; Carbonelli, Michele (Frontiers in Neurology, 2018)
Melanopsin retinal ganglion cells (mRGCs) are intrinsically photosensitive RGCs that mediate many relevant non-image forming functions of the eye, including the pupillary light reflex, through the projections to the olivary pretectal nucleus. In particular, the post-illumination pupil response (PIPR), as evaluated by chromatic pupillometry, can be used as a reliable marker of mRGC function in vivo. In the last years, pupillometry has become a promising tool to assess mRGC dysfunction in various neurological and neuro-ophthalmological conditions. In this review we will present the most relevant findings of pupillometric studies in glaucoma, hereditary optic neuropathies, ischemic optic neuropathies, idiopathic intracranial hypertension, multiple sclerosis, Parkinson's disease, and mood disorders. The use of PIPR as a marker for mRGC function is also proposed for other neurodegenerative disorders in which circadian dysfunction is documented.